PENGARUH ZAKAT PRODUKTIF TERHADAP PRODUKTIVITAS DAN PROFITABILITAS USAHA MIKRO MUSTAHIK BAZNAS KOTA BLITAR - Luthfi Hasanain ; Atu Bagus Wiguna, SE., ME
Zakat has a very strategic role in efforts to alleviate poverty or economic _x000D_ development. Zakat can be managed not only consumptively, but to maximize its _x000D_ potential, zakat can also be managed productively which will make mustahik _x000D_ continue to produce something by using it as capital in running a micro business. _x000D_ Distribution of productive zakat is one of the programs run by BAZNAS in Blitar _x000D_ City in the hope that it can help with the problem of the capital of mustahik micro _x000D_ businesses. Therefore, this study would like to see how the effect of productive _x000D_ zakat distributed by BAZNAS Blitar on mustahik micro-businesses, which in this _x000D_ case is seen in terms of productivity and profitability. This research is a _x000D_ quantitative study using path analysis methods. The results showed that _x000D_ productive zakat had a significant effect on productivity and profitability of _x000D_ mustahik micro-businesses. _x000D_ Keywords: Productive zakat, productivity, profitability, micro business